Strategi Komunikasi Pemasaran Digital Pinjam Wifi Global Melalui Pemanfaatan Media Sosial Instagram untuk Membentuk Minat Konsumen - Susanto, Agung; Tomohardjo, Irmulansati; Budianto, Heri (Universitas Batanghari Jambi, 2025)
This study aims to analyze Pinjam Wifi's marketing communication strategy through Instagram using the AISAS (Attention, Interest, Search, Action, Share) model. Qualitative methods and case studies, data were collected through interviews, observations, and internal company documents. The results of the study indicate that Pinjam Wifi carries out the AISAS stages with strategies such as paid advertising (attention), promo and discount campaigns (interest), use of hashtags (search), creation of various types of content to form engagement (action), and customer reviews shared on Instagram (share). In addition, the push & pull marketing strategy is implemented through paid advertising, retail distribution, and business content. This strategy has succeeded in forming product sales and Pinjam Wifi's Instagram engagement rate.